An Analysis of the Construction of Ethnic Themes in Guangxi Orchestra Works: Taking Luo-Yue Culture as an Example - Yilin, Wang; Jirajarupat, Phakamas; LingLing, Liu (Journal of Roi Kaensarn Academi, 2024)
China’s thousand-year history has left behind a long tradition of ethnic culture and rich cultural products. Some of the essence of ethnic culture has been used in various artistic creations, creating unique artworks with ethnic characteristics. Orchestral music plays an important role in the field of music and art in China, and plays an important role in promoting the development and influence of national music. To better reflect ethnic ideas, customs, and lifestyles, ethnic elements are integrated into music vocabulary, making the creation of orchestral music more ethnic, diverse, and contemporary. This paper will use literature research and case study methods to explore the nationalistic connotations of the thematic construction of Guangxi orchestral music. From the perspective of the theme creation of orchestral works, the theme background, content, and techniques of the works are analyzed one by one, revealing the important position and profound significance of ethnic themes in orchestral music creation. It is hoped that this research can promote the development of Guangxi orchestral music creation, provide new perspectives for the theoretical research of Guangxi orchestral music, and inject new vitality into the promotion of ethnic culture.